Physiological linkage and affective dynamics in dyadic interactions between adolescents and their mothers. Issue 5 (10th May 2018) - McKillop, Hannah N.; Connell, Arin M.
Abstract: This study examined physiological linkage (specifically, linkage in respiratory sinus arrhythmia; RSA) between parents and youth (aged 11–17) across conflict and fun activity discussion tasks. We also examined whether observed, momentary negative affect or parental depressive symptoms, would moderate patterns of RSA linkage across the interaction tasks. RSA linkage was assessed using a multilevel actor–partner interdependence model (APIM). Participants were 59 mother–adolescent dyads, including mothers with or without clinically significant depressive symptoms. Both mothers and teens evidenced stable RSA over time ( actor effect), although the stability of maternal RSA was moderated by maternal depression, with maternal depressive symptoms related to slower RSA return to baseline. There was a significant partner influence on youth RSA, with maternal RSA positively related to subsequent youth RSA. However, this effect was moderated by maternal depression and maternal negative affect (NA), with low maternal depression/low maternal NA related to dyadic synchrony, whereas high depression or high NA led to attenuation of this relationship. Results demonstrate the importance of understanding the dynamic and complex nature of family interactions in the context of depression.